(untitled) (KYAMC Journal, 2023)
Background: Pregnancy-induced hypertension (PIH) is a relatively common pregnancy disorder that causes variable maternal and fetal problems. This may increase the number of perinatal asphyxia, sepsis, still birth etc. It also has a significant affect on birth weight which is also related to gestational age. Objectives: To observe the impact of pregnancy induced hypertension on their newborn babies and compare the findings with the babies of normotensive mother. Materias and Methods: This case control study was conducted from July 2016 to December 2016. The study group was selected from the babies of pregnancy induced hypertension (PIH) mothers and control group selected from babies of a normotensive mother attending in Obstetrics department of Dhaka Medical College Hospital, Dhaka having the inclusion and exclusion criteria. The total number of 100 neonates were included consecutively in this study. 50 neonates born to mothers with pregnancy-induced hypertension were grouped as cases and 50 neonates born to normotensive mothers were grouped as control. Results: The study revealed that, the highest frequency of neonatal morbidities were perinatal asphyxia (22%) among the babies of PIH mother. Stillbirth it was found 12 % . The duration of pregnancy were also affected by PIH where most of the babies were preterm (88%) and complete-term pregnancy found only (12%). It should be mentioned that those mother having history of preeclampsia delivered more premature babies (p <0.001). Another important outcome birth weight related to gestational age was also very important which were measured as the highest for SGA 92% and AGA 8%. The weight of the baby were significantly (p<0.001) reduced in those who had a history of PIH and the mean weight was 1592.78 ± 470.06. Conclusion: Prematurity, Small for gestational-age babies and perinatal asphyxia are more common in Pregnancy induced hypertension group than in the normotensive group. KYAMC Journal Vol. 13, No. 04, January 2023: 204-207